Bats join the ranks of oxpeckers and cleaner fish as partners in a pest‐reducing mutualism. (3rd February 2019) - Palmer, Meredith S.; Krueger, Jim; Isbell, Forest
Abstract: While antagonistic species interactions such as predation or competition have a long history of study, positive inter‐species interactions have received comparatively little attention. Mutualisms and commensalisms appear to be widespread in the animal kingdom, with examples of mammals, birds, fish, and reptiles from around the world engaging with other species in evidentially beneficial ways. Cleaning mutualism is a specific type positive inter‐species interaction in which one species removes and feeds upon parasites infesting the other. Here, we document a new subset of positive inter‐species "cleaning" interactions, in which one partner benefits from and reduces the abundance of pest species attracted by but not attached to their host. We observed in person and in camera trap footage numerous instances of insectivorous bats associating with white‐tailed deer ( Odocoileus virginianus ) and feeding on the swarms of biting flies attracted to these large mammals. We call for the increased reporting of positive inter‐species associations to better our understanding of the mechanisms leading to the formation of these interactions and the effects that these relationships may for the structuring of ecological communities.